2013
DOI: 10.1002/psc.2597
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the oxyanion hole of trypsin for promoting the reverse of proteolysis

Abstract: Although proteases are capable of synthesizing peptide bonds via the reverse of proteolysis, they are not proficient at peptide fragment ligation. Further manipulations are needed to shift the native enzyme activity from the cleavage to the synthesis of peptides especially when longer peptides or even proteins are the target molecules of the reaction. This account reports on the synthetic potential of trypsin variants with engineered oxyanion holes mutated by proline mutations, which were designed to minimize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Moreover, the side chain amide nitrogen of N94 and the backbone of S11 and A55 form the oxyanion hole, which coordinates the carbonyl of the acyl-enzyme complex (Figure B). It was previously reported that mutation of a residue of the oxyanion hole in a serine protease led to 80-fold decreased deacylation rates, resulting in stabilization of the acyl-enzyme intermediate and reduced hydrolase activity. MsAcT oxyanion hole residues were therefore very important targets in our study.…”
Section: Resultsmentioning
confidence: 79%
“…Moreover, the side chain amide nitrogen of N94 and the backbone of S11 and A55 form the oxyanion hole, which coordinates the carbonyl of the acyl-enzyme complex (Figure B). It was previously reported that mutation of a residue of the oxyanion hole in a serine protease led to 80-fold decreased deacylation rates, resulting in stabilization of the acyl-enzyme intermediate and reduced hydrolase activity. MsAcT oxyanion hole residues were therefore very important targets in our study.…”
Section: Resultsmentioning
confidence: 79%
“…Also, it does not require hazardous substances and may reduce wastes drastically. [16][17][18][19][20] Therefore, it has been included among the clean, or environmentally friendly, technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in oxyanion holes could affect the activity performance of trypsin. For example, a mutant Gln192Pro was demonstrated to have a prominently reduced hydrolytic activity and improved ligase activity [340]. Moreover, a quadruple mutant Lys60Glu/Asn143His/Glu151His/Asp189Lys, termed trypsiligase, adopts a partially disordered zymogen-like state with an activation domain lacking ligand [341].…”
Section: Trypsiligasementioning
confidence: 99%